RETRACTED: Bactericidal/Permeability-Increasing Protein Improves Cognitive Impairment in Diabetic Mice via Blockade of the LPS-LBP-TLR4 Signaling Pathway - Sun, Qin; Li, Tingxin; Li, Yamei; Wei, Lingling; Zhang, Min; Deng, Shaoping (Frontiers in Physiology, 2021)
Emerging evidence suggests that the bactericidal/permeability-increasing protein (BPI) is involved in the process of cognitive impairment in diabetes. However, its underlying mechanism remains elusive. In this study, we found that BPI affects cognitive impairment due to diabetes through the lipopolysaccharide (LPS)-lipopolysacharide-binding protein (LBP)-toll-like receptor 4 (TLR4) signaling pathway. We examined the expression of BPI, LPS, LBP, CD14, and TLR4 in established mouse models of diabetes induced by high-fat diet (HFD) in combination with streptozotocin (STZ). Diabetic mice were then injected with adeno-associated-virus carrying BPI overexpression vectors and LPS. Fasting blood glucose, plasma insulin, and serum levels of inflammatory factors were examined. Then, glucose tolerance and, insulin resistance tests were used to measure systemic insulin sensitivity. Next, hippocampal tissue injury and cell apoptosis were examined by hematoxylin-eosin (HE) and terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) staining. Diabetic mice displayed increased LPS expression and activation of the LPS-CD14-TLR4 signaling pathway. HFD mice following LPS treatment showed significantly increased serum levels of tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6, and expressions of Bcl-2-associated X protein (Bax) and Aβ but decreased expression of Bcl-2 in hippocampal tissues, as well as enhanced fasting blood glucose, plasma insulin, glucose tolerance, insulin tolerance, cell apoptosis, aggravated hippocampal tissue injury and, ultimately, cognitive impairment. However, overexpression of BPI was able to rescue the aforementioned phenotypes driven by LPS treatment. Taken together, BPI could potentially provide relief from cognitive impairment in diabetic mice by disrupting the LPS-LBP-TLR4 signaling pathway, underscoring a possible alternative therapeutic strategy against the cognitive impairment associated with diabetes.